Monetary and fiscal policy mix connectivity towards the business cycle in Indonesia - Regina Niken Wilantari; Imro'atul Husna Afriani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This research is based on the magnitude of the influence of monetary and fiscal aspects, namely the money supply, exchange rates, government spending, and taxes on the business cycle in Indonesia. This study aims to examine the effect of the connection between the monetary and fiscal policy mix on the business cycle in Indonesia. For analysis purposes, secondary data was used in the form of time-series data from 1970–2017. The method used is the Vector Error Correction Model (VECM) to see long-term and short-term relationships. In the estimation results, it is found that in the long-term period, the monetary variables (money supply and exchange rates) and fiscal variables (government expenditures and taxes) have a significant positive effect on the business cycle in Indonesia.In contrast, the monetary variables that have a significant effect in the short-term period are only the amount variable money supply. There are no fiscal variables that have a significant effect on the business cycle in Indonesia. The interaction of monetary and fiscal policies is still effectively implemented in Indonesia.